Role of attractive forces in the relaxation dynamics of supercooled liquids - Chattoraj, Joyjit (2020)
The attractive tail of the intermolecular interaction affects very weakly the structural properties of liquids, while it affects dramatically their dynamical ones. Via the numerical simulations of model systems not prone to crystallization, both in three and in two spatial dimensions, here we demonstrate that the nonperturbative dynamical effects of the attractive forces are tantamount to a rescaling of the activation energy by the glass transition temperature T_{g}: systems only differing in their attractive interaction have the same structural and dynamical properties if compared at the same value of T/T_{g}.